Hemostatic Agents in Orthopedic Surgery. Issue 2 (May 2023) - Tanghe, Kira K.; Chalmers, Brian P.; Blevins, Jason L.; Figgie, Mark P.; Carli, Alberto V.; Agrusa, Christopher J.; Sculco, Peter K.; Gausden, Elizabeth B.
Controlling blood loss is a crucial aspect of orthopedic surgery. Hemostatic agents can be used intraoperatively in combination with antifibrinolytics as part of an overall strategy to limit blood loss. Several new hemostatic agents have recently come to the market designed specifically for vascular surgery but have found uses in other surgical fields, including orthopedics. This article reviews the mechanisms of action and best uses of various mechanical hemostats, active hemostats, flowable hemostats, and fibrin sealants for achieving hemostasis in orthopedic surgery. Mechanical and active hemostats have been reported to successfully decrease blood loss from cancellous bone, capillaries, and venules. Flowable hemostats are generally favorable for use in small spaces where the swelling capabilities of mechanical and active hemostats can be detrimental to surrounding structures. Sealants are best used for closing defects in tissues.